2008
DOI: 10.1103/physrevb.77.035103
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofRAuSn(R=Sc, Ce, Gd, Er, and Lu) investigated with x-ray photoelectron spectroscopy and band structure calculati

Abstract: We have investigated the electronic structure of the intermetallic compounds ScAuSn, CeAuSn, GdAuSn, ErAuSn, and LuAuSn using x-ray photoelectron spectroscopy and band structure calculations. We find good general agreement between the experimental and calculated valence band spectra, provided that the spin-orbit interaction in the Au bands as well as correlation effects in the open rare-earth 4f shell are included in the calculations. The rare-earth 4f and Au 5d have well identified spectral features far away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
6
7
0
Order By: Relevance
“…We would like to note that the main peak of the calculated Pt 5d DOS is positioned at a some- what lower binding energy than that of the experimental difference spectrum. Similar small deviations have been observed in other intermetallic materials 23,24 and can be attributed to the inherent limitations of mean-field methods like the LDA to calculate the dynamic response of a system. Figure 5 shows the difference of the spectrum taken at 190 eV and the rescaled spectrum at 700 eV.…”
supporting
confidence: 74%
“…We would like to note that the main peak of the calculated Pt 5d DOS is positioned at a some- what lower binding energy than that of the experimental difference spectrum. Similar small deviations have been observed in other intermetallic materials 23,24 and can be attributed to the inherent limitations of mean-field methods like the LDA to calculate the dynamic response of a system. Figure 5 shows the difference of the spectrum taken at 190 eV and the rescaled spectrum at 700 eV.…”
supporting
confidence: 74%
“…The electronic structure studied by XPS measurements and calculated ones were found in agreement in RAuSn (R=Sc, Ce, Gd, Er, Au) [533]. The results shows that R 4f and Au 5d…”
Section: Electronic Structure Calculations and Electron Spectroscopysupporting
confidence: 60%
“…well defined identified spectral features far away from the Fermi level [533]. It has been observed that spectral weight in the vicinity of the Fermi level is mainly contributed by Au/Sn sp and R spd bands [533].…”
Section: Electronic Structure Calculations and Electron Spectroscopymentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the bond shortening effect of the p σ –p σ σ‐bonding should be partially reduced in the T 2 dimer based on the d 10 s 2 p 2 configuration because of the presence of two extra electrons in the p π –p π π‐bonding levels. Experimentally, the T – T bond lengths of the T 2 dimers in AE 5 T 3 are Au–Au = 2.906 Å 15, Ag–Ag = 2.774 Å 16, Hg–Hg = 3.300 Å 17, Cd–Cd = 2.983 Å 18, Zn–Zn = 2.633 Å 19. These observed bond lengths ( r obs ) are shorter than the lengths ( r sum ) expected from the sum of the calculated atomic radii 27 (i.e., 3.48, 3.30, 3.42, 3.22, and 2.84 Å, respectively).…”
Section: Resultsmentioning
confidence: 98%